Does the Individual Environment, Social, Government Score Could Mitigate the Financial Distress Risk ? - Hutauruk, Carolina Ito; Nurazi, Ridwan (East Asian Journal of Multidisciplinary Research, 2024)
This research paper investigates the impact of the Individual Environment, Social, Government (ESG) score on mitigating financial distress risk. The study examines the individual components of the ESG score, specifically focusing on the environmental, social, and government scores. The results indicate that while the environmental and government scores have a significant effect toward the financial distress risk, the social score does not show a significant impact. These findings suggest that organizations should prioritize environmental and government factors when assessing and managing financial distress risk while considering the limited impact of social factors. This study provides valuable insights for decision-makers in formulating effective risk mitigation strategies.